Contesting inclusive urbanism in a divided city: The limits to the neoliberalisation of Cape Town's energy system. (November 2014) - Swilling, Mark
The struggles to define and implement an inclusive non-racial urbanism in South Africa after democratisation in 1994 occurred during the heyday of world-wide diffusion of unevenly developed neoliberalisation processes. This case study of the complexities of transforming Cape Town's energy sector analyses the consequences of these contradictory trajectories by tracking the dynamics of four urbanism typologies: inclusive, splintered, green and slum urbanism. It is argued that, while the imperatives of deracialisation reinforced inclusive trends, neoliberalisation processes reinforced splintered urbanism and its consequences, namely slum urbanism. These dynamics were then overdetermined by environmental changes that have introduced green urbanism as a new arena of contestation.